The Combination of D-TACE-HAIC, Lenvatinib, and PD-1 Inhibitors Shows Significant Clinical Efficacy in Patients with Unresectable Hepatocellular Carcinoma - Wu Y; Zhu J; Zhang H; Xia N (Cancer Management and Research)
Yintao Wu,* Jianyong Zhu,* Hong Zhang, Nianxin Xia Senior Department of Hepato-Pancreato-Biliary Surgery, the First Medical Center of PLA General Hospital, Beijing, 100853, People’s Republic of China*These authors contributed equally to this workCorrespondence: Nianxin Xia, Senior Department of Hepato-Pancreato-Biliary Surgery, the First Medical Center of PLA General Hospital, Beijing, 100853, People’s Republic of China, Email doctorxnx@163.comPurpose: This study was developed to compare the efficacy of combined D-TACE-HAIC + lenvatinib + PD-1 inhibitor treatment to that of TACE + sorafenib treatment for patients with intermediate and advanced HCC.Patients and Methods: Here, a retrospective analysis of patients with unresectable HCC who underwent transarterial chemoembolization (TACE) from March 2018 to March 2022 at the our hospital was conducted. In total, 60 patients underwent treatment with drug-eluting beads-TACE-hepatic arterial infusion chemotherapy (D-TACE-HAIC) combined with lenvatinib and PD-1 inhibitors (Group A), while 21 underwent combined TACE and sorafenib treatment (Group B).Results: In this study cohort, the rate of surgical conversion in Group A was significantly higher than that in Group B (33.3% vs 9.5%). As per the Revised Evaluation Criteria for Clinical Efficacy in Solid Tumors (mRECIST) criteria, the objective remission rate in Group A was significantly higher than that in Group B (86.6% vs 33.4%). Group A also exhibited significantly higher rates of overall adverse events including hypertension, abdominal pain, leukopenia, thrombocytopenia, and hypoproteinemia as compared to Group B, although the incidence of hand-foot syndrome in Group A was significantly reduced as compared to Group B (13.3% vs 42.8%). The median progression-free and overall survival (PFS and OS) of patients in Group A were 13.2 and 28.8 months, with both being significantly higher than the corresponding intervals in Group B (5.7 and 10.8 months, respectively). Cox multivariate analyses identified combination D-TACE-HAIC + lenvatinib+ PD-1 inhibitor treatment as being independently associated with patient PFS and OS.Conclusion: In summary, D-TACE-HAIC + lenvatinib + PD-1 inhibitor treatment exhibits a favorable safety profile, outperforming TACE + sorafenib treatment for unresectable HCC patients while improving overall rates of translational efficacy, increasing rates of surgical conversion, prolonging patient survival, and conferring long-term survival benefits.Keywords: unresectable hepatocellular carcinomas, drug-eluting beads-transarterial chemoembolization-hepatic arterial infusion chemotherapy, clinical efficacy, prognosis